2008
DOI: 10.1007/s11606-008-0679-9
|View full text |Cite
|
Sign up to set email alerts
|

Development and Pilot Evaluation of Literacy-Adapted Diabetes and CVD Education in Urban, Diabetic African Americans

Abstract: Development of patient education meeting very low literacy criteria was feasible, effective for knowledge acquisition, and highly acceptable irrespective of literacy level.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
35
0

Year Published

2009
2009
2014
2014

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 24 publications
(36 citation statements)
references
References 11 publications
1
35
0
Order By: Relevance
“…Patient satisfaction and usability were assessed using a series of nine items on which participants rate, on a scale from 1 (least) to 5 (most), ease of use, ease of understanding, usability, helpfulness, and satisfaction with the education program and workbooks. 13,14 Data Analysis Categorical variables were described using frequency distributions, and continuous variables were described using mean and standard deviation, for the entire study sample and by intervention assignment. Distributional differences in these variables between intervention groups were evaluated using chi-square test for categorical variables and analysis of variance for continuous variables.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Patient satisfaction and usability were assessed using a series of nine items on which participants rate, on a scale from 1 (least) to 5 (most), ease of use, ease of understanding, usability, helpfulness, and satisfaction with the education program and workbooks. 13,14 Data Analysis Categorical variables were described using frequency distributions, and continuous variables were described using mean and standard deviation, for the entire study sample and by intervention assignment. Distributional differences in these variables between intervention groups were evaluated using chi-square test for categorical variables and analysis of variance for continuous variables.…”
Section: Methodsmentioning
confidence: 99%
“…Further details of the educational content are described elsewhere. 13,14 The interventions and materials were adapted for low literacy and accessibility using available guidelines. [15][16][17][18] Patient workbooks also utilized colors (red/green) and symbols (thumbs up/thumbs down) for key concepts.…”
Section: Diabetes and Cvd Education Modulementioning
confidence: 99%
See 1 more Smart Citation
“…Before any intervention, patients with low literacy generally score lower on tests of diabetes knowledge than patients with higher literacy. 6,7 As discussed above, this may be important in the pathway that links low literacy with worse diabetes outcomes.…”
Section: Key Question 1: What Interventions Improve Knowledge Of Diabmentioning
confidence: 98%
“…[6][7][8][9][10][11][12] Overall, five of the six studies showed improvement in diabetes knowledge as measured by a significant improvement in a diabetes knowledge test. Each of the studies used a different diabetes knowledge test to measure diabetes knowledge.…”
Section: Key Question 1: What Interventions Improve Knowledge Of Diabmentioning
confidence: 99%